Contribuição do Departamento de Educação da Universidade Católica de Goiás para redefinição do curso de pedagogia - Andrade, Eduvirgens Carlita de (1983)
That's an analysis of the development that brings out the possibilities of a best comprehension of the story of the Education Department in the period of 1972 to 1983. The principal aim of that careful study i s to emphasize the great effort and the contribuition of that departament in order to outline new and best objectives of the Pedagogical course. The procedure to reach this objective was the study of papers, documents concerned with Educational norms, Resoluctions, Decrees, Laws and also the valuation of specialists and of professionals of the area. We also included to this group the professional of the area were the ones who had the responsability of this educational sector of the government at this time. The participation in Seminars, Conferences and Congresses was part of the work developed in this research. That study is the result of a hard work and that's now recognized for the Educational Departament of International area. That work make also possible to give a new direction to the Pedagogical Course, chinging the earlier sets for the ones according to the real necessity of the schoolar Brazilian System.